Implementasi Prinsip Kehati-Hatian (Prudential) dalam Pemberian Kredit Pembiayaan Konsumen Pada PT. Clipan Finance Indonesia Tbk. - I Gede Agus Putrayasa; I Nyoman Putu Budiartha; Desak Gede Dwi Arini (Jurnal Konstruksi Hukum, 2020)
Indonesia is a developing country, in the last decade it has progressed quite rapidly, even though this progress was marked by difficult times because it had just emerged from a prolonged economic crisis. The purpose of this study is to determine how the implementation of the principle of prudence (prudential) in providing consumer financing credit at PT. Clipan Finance Indonesia Tbk. And what actions are PT. Clipan Finance Indonesia Tbk. if there is a delay in installment payments by consumers, causing bad credit. The research method used in this research is empirically by looking for information at PT. Clipan Finance Indonesia Tbk. Through interviews with the addition of related literature, which is then processed descriptively qualitatively. Data collection techniques using primary data sources (interviews) and secondary data sources (literature). The results showed the implementation of the prudential principle in providing consumer financing credit at PT. Clipan Finance Indonesia Tbk. is to apply the five of credit or 5 Cs, namely character, capacity, capital, collateral, and conditions of economy, in which the application of these principles applies two methods by combining consideration and empirical methods. This method fully emphasizes the credit analyst's analytical expertise. After receiving consideration, the credit analyst prepares a standard amount of evaluation value according to the considerations above to pass or reject a credit request. Actions taken by PT. Clipan Finance Indonesia Tbk. if there is a delay in installment payments which causes problem / bad credit is PT. Clipan Finance Indonesia Tbk. will give warning letters from I to III with certain stages, after these stages are unsuccessful PT. Clipan Finance Indonesia Tbk. negotiate with consumers and find the best solution.